Sociodemographic and geospatial associations with community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) infections in a large Canadian city: an 11 year retrospective study - Victoria C. Gill; Irene Ma; Maggie Guo; Dan B. Gregson; Christopher Naugler; Deirdre L. Church (BMC, 2019)
Abstract Background The first Canadian outbreak of community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) was identified in 2004 in Calgary, Alberta. Using a novel model of MRSA population-based surveillance, sociodemographic risk associations, yearly geospatial dissemination and prevalence of CA-MRSA infections over an 11 year period was identified in an urban healthcare jurisdiction of Calgary. Methods Positive MRSA case records, patient demographics and laboratory data were obtained from a centralized Laboratory Information System of Calgary Laboratory Services in Calgary, Alberta, Canada between 2004 and 2014. Public census data was obtained from Statistics Canada, which was used to match with laboratory data and mapped using Geographic Information Systems. Results During the study period, 52.5% of positive MRSA infections in Calgary were CA-MRSA cases. The majority were CMRSA10 (USA300) clones (94.1%; n = 4255), while the remaining case (n = 266) were CMRSA7 (USA400) clones. Period prevalence of CMRSA10 increased from 3.6 cases/100000 population in 2004, to 41.3 cases/100000 population in 2014. Geospatial analysis demonstrated wide dissemination of CMRSA10 annually in the city. Those who are English speaking (RR = 0.05, p <  0.0001), identify as visible minority Chinese (RR = 0.09, p = 0.0023) or visible minority South Asian (RR = 0.25, p = 0.015), and have a high median household income (RR = 0.27, p <  0.0001) have a significantly decreased relative risk of CMRSA10 infections. Conclusions CMRSA10 prevalence increased between 2004 and 2007, followed by a stabilization of cases by 2014. Certain sociodemographic factors were protective from CMRSA10 infections. The model of MRSA population-surveillance and geomap outbreak events can be used to track the epidemiology of MRSA in any jurisdiction.